Restorative Justice and Police Discretion for Low-Income and Vulnerable Groups in Indonesia and India - Aprialdi Aprialdi; Herlita Eryke; Amit Kumar Kashyap; Ousu Mendy (RechtIdee, 2026)
Study Objective: This article examines how restorative justice and police discretion can expand, rather than ration, access to justice for low-income and vulnerable groups in Indonesia.Method/Approach: It uses normative-comparative legal research to compare Indonesia's contemporary framework with India's Bharatiya Nagarik Suraksha Sanhita 2023.Novelty: this research is novel in that it does not treat India's plea-bargaining and case-settlement mechanisms as synonymous with police-led restorative justice. Instead, it questions what safeguards can prevent discretionary settlements from reproducing poverty and secondary victimization.Findings: The analysis finds that India now has a stronger legal basis for restorative justice across the criminal process, but the police's role as first contact still creates material risks, including inconsistencies, pressure to settle cases, and unequal access to legal counsel. India offers a useful contrast because its plea-bargaining framework relies on judicial verification of voluntariness, eligibility determination, victim participation, and compensation, while excluding certain socially sensitive offenses.Conclusion: This article proposes a vulnerability-based discretionary framework for Indonesia: early legal aid, independent counsel, screening for power and security imbalances, proportional and non-monetary reparation options, written reasons, review, and public aggregate reporting. Restorative justice should operate as a voluntary, accountable, and redress-the-harm pathway without punishing poverty.